Implementation Provider Business Strategies Service Tour (Literature Study of SMEs Travel Bureau Malang City) - Immanuel U Osijo; Sudarmiatin (Indonesian Journal of Business Analytics, 2023)
This research was conducted to find out the effort made by the Travel Bureau in achieving competitive advantage in its business. The focus of this research is on the MSME business strategy of travel and tourism bureaus in Malang City. The research was conducted by studying the literature listed on Google Scholar. This research uses a Systematic Literature Review with the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) method. From the results of the search for articles that are considered relevant, analyzed by the author, there are 7 articles that are worthy of analysis. The results of the analysis of the literature review show that the focus of the business strategy of the UMKM Travel Bureau in Malang City is Price-oriented, Application of the Halal Tourism concept, Health Orientation, Digital Information Services, Expansion of the segment to foreign tourists,Through this study it is hoped that it will be able to make a positive contribution related to the marketing strategy that has been carried out by SMEs Travel Bureau actors and can be used as a reference by researchers who are interested in the same field so that they are more creative in identifying research from different points of view.